2021
DOI: 10.3390/fib9110073
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Evaluation of Replacing Minimum Web Reinforcement with Discrete Fibers in RC Deep Beams

Abstract: This study investigates the possibility of replacing the minimum web reinforcement in deep beams with discrete fibers. Additionally, the equivalent dosage of fibers required to obtain similar performance of the deep beam with minimum web reinforcement is investigated. Deep beams made of plain concrete with no fibers, beams with minimum web reinforcement as per AASHTO LFRD recommendations (0.3% in both horizontal and vertical), and with a 0.5% volume fraction of steel, macro-synthetic and hybrid fibers are test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It can be observed that the workability of recycled aggregate concrete is still improved with the incorporation of steel fiber and superplasticizer. Although it has also been reported that steel fibers decreased workability [36] while superplasticizer increased workability [51], the combined substitution ratio of steel fibers, GGBS, and superplasticizer showed better workability concrete. Figure 5 shows the fresh density of concrete with varying dosages.…”
Section: Slump and Fresh Densitymentioning
confidence: 81%
See 4 more Smart Citations
“…It can be observed that the workability of recycled aggregate concrete is still improved with the incorporation of steel fiber and superplasticizer. Although it has also been reported that steel fibers decreased workability [36] while superplasticizer increased workability [51], the combined substitution ratio of steel fibers, GGBS, and superplasticizer showed better workability concrete. Figure 5 shows the fresh density of concrete with varying dosages.…”
Section: Slump and Fresh Densitymentioning
confidence: 81%
“…Furthermore, dynamic performance under impact load also showed a positive response with fibers [35]. Some studies have reported that fiber improves tensile strength more effectively than compressive strength [20,36]. According to a past study, 0.3% web reinforcement (horizontal and vertical direction) improved peak load 25% more than compared to plain concrete [37].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations